THE USE OF MULTIMODAL COMMUNICATIVE METHODS IN TEACHING EFL: LITERATURE REVIEW - Ega Nur Fadillah; Sri Widiastuti; Muhammad Yusuf Hadi Putra (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
This research aims to undergo a comprehensive literature review on the use of multimodal communicative methods in teaching English as a foreign language (EFL). The multimodal communicative method integrates diverse types of media and communication modalities, such as text, images, audio, and video, to enhance the effectiveness of English language learning. This article will present an in-depth review of the basic concept of the multimodal communicative method, the benefits of its use in EFL teaching contexts, as well as relevant research results. By understanding this concept, English language educators can improve the quality of their teaching and assist students in achieving a deeper and more sustainable understanding of the language. This research has the potential to provide valuable insights in the development of English language education in the growing digital age.